Ceiba pentandra, Nigella sativa and their blend as prospective feedstocks for biodiesel - Yunus Khan, T.M.; Atabani, A.E.; Badruddin, I.A.; Ankalgi, R.F.; Khan, T.K.M.; Badarudin, A. (Elsevier, 2015)
There are more than 350 oil-bearing crops identified as potential sources for biodiesel production around the globe. The wide range of available feedstocks for biodiesel production represents one of the most significant factors for producing biodiesel. The current research work is carried out on fuel properties of biodiesel prepared from the non-edible oils of Ceiba pentandra, Nigella sativa and their mixture. N. sativa is believed to be investigated for the first time as a biodiesel feedstock while C. pentandra has been reported recently in few studies. Owing to higher acid value, acid-esterification and alkali-transesterification processes have been carried out for biodiesel production. The fuel properties of C. pentandra methyl ester (CPME), N. sativa methyl ester (NSME) and their feedstock mixture (NSME/CPME) are determined. It has been found that the produced biodiesel from respective feedstocks matches the properties set by ASTM 6751 standards. However, the fuel properties of the C pentandra biodiesel exhibited better calorific value, viscosity and flash point while N. sativa exhibited excellent cold flow properties and oxidation stability. (C) 2014 Elsevier B.V. All rights reserved.